(untitled) (Circe de clásicos y modernos, 2018)
America, traditionally, has offered to the history of the Company very varied journals. Among the most outstanding American testimonies, mention should be made of the diary of José Manuel Peramás, catalan jesuit from the province of Paraguay, in its two versions: the first in Spanish (Narración de lo sucedido a los jesuitas del Paraguai) and the second in Latin (Annus patiens siue Ephemerides). The Narración is the most widespread and consulted. The Annus Patiens, practically unknown for the academic world, it has circulated, especially among historians, in Giuseppe Boero’s version. This time we will focus our attention on the analysis of the translation strategies put into play by the Italian Jesuit, on the basis of the concepts of rewriting and manipulation.